Identification and validation of the role of c-Myc in head and neck squamous cell carcinoma - Zhao, Sufeng; An, Li; Yang, Xudong; Wei, Zheng; Zhang, He; Wang, Yufeng (Frontiers in Oncology, 2022)
Background Many studies have shown that c-Myc plays a critical role in tumorigenesis. However, the molecular role of c-Myc in head and neck squamous cell carcinoma (HNSC) remains unclear. Methods Several biological databases, including UALCAN, TIMER2.0, TCGAportal, GEPIA, KM plotter, OncoLnc, LinkedOmics, GSCA, and TCIA, were used to analyze the molecular role of c-Myc in HNSC. The expression levels of c-Myc were validated by real-time PCR (RT–PCR) and Western blot in CAL-27 cells. Results The expression of c-Myc mRNA were significantly increased in HPV-negative HNSC tissues. The expression of c-Myc gene level was correlated with TP53 mutation status. HNSC also showed hypomethylated c-Myc compared with normal tissues. c-Myc was identified as an ominous prognostic factor for HNSC patients and correlated with immune infiltrating levels. Moreover, high c-Myc expression was associated with decreased expression of a series of immune checkpoints, resulting in a dampened immune response. c-Myc potentially mediated IL-17 signaling pathway and Th1 and Th2 cell differentiation. Inhibition of c-Myc expression increased apoptosis of CAL-27 cells. Conclusions These findings suggest a new mechanism of c-Myc in the prognosis of HNSC, implying the potential of c-Myc as a therapeutic target for HNSC patients.